2023
DOI: 10.1021/acsenergylett.2c02434
|View full text |Cite
|
Sign up to set email alerts
|

Superwettable High-Voltage LiCoO2 for Low-Temperature Lithium Ion Batteries

Abstract: Lithium-ion batteries with both low-temperature (low-T) adaptability and high energy density demand advanced cathodes. However, state-of-the-art high-voltage (high-V) cathodes still suffer insufficient performance at low T, which originates from the poor cathode–electrolyte interface compatibility. Herein, we developed a shallow surface Zr-doped and Li+ conductive Li2Zr­(PO4)2 (LZPO) interspersed massage-ball-like LiCoO2 (LZPO-LCO). The surface-interspersed LZPO can induce an electrolyte superwettability of LZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In the final charging stage, the R ct value of Bi 0.67 NbS 2 shows a slight increase compared to the OCV state, demonstrating its stable crystal structure with small distortion. [67,68] In addition, the GITT profiles are presented (Figure 4j; Figures S21a and S22a, Supporting Information). The Bi 0.67 NbS 2 anode displays intermediate Na + diffusion coefficients between those of Bi and NbS 2 (Figure 4k; Figures S21b and S22b, Supporting Information), which illustrates a facilitative Na + mobility of Bi 0.67 NbS 2 benefited from Nb−S host framework.…”
Section: Na + Storage Performance and Kinetic Analysesmentioning
confidence: 99%
“…In the final charging stage, the R ct value of Bi 0.67 NbS 2 shows a slight increase compared to the OCV state, demonstrating its stable crystal structure with small distortion. [67,68] In addition, the GITT profiles are presented (Figure 4j; Figures S21a and S22a, Supporting Information). The Bi 0.67 NbS 2 anode displays intermediate Na + diffusion coefficients between those of Bi and NbS 2 (Figure 4k; Figures S21b and S22b, Supporting Information), which illustrates a facilitative Na + mobility of Bi 0.67 NbS 2 benefited from Nb−S host framework.…”
Section: Na + Storage Performance and Kinetic Analysesmentioning
confidence: 99%
“…Huang and co-workers enhance electrolyte-wettability of LCO by coating a more electrolyte-wettable materials and constructing a specific surface microstructure. [74] As a precursor material, Li + conduc- Reproduced with permission. [73] Copyright 2015, American Chemical Society.…”
Section: Metallic Oxide For Cathode Of Metal Ion Batteriesmentioning
confidence: 99%
“…e) The contact angle of each sample with the electrolyte at room temperature. Reproduce with permission [74]. Copyright 2023, American Chemical Society.…”
mentioning
confidence: 99%
“…For example, Huang's group reported a Zr-doped and Li + conductive Li 2 Zr(PO 4 ) 2 interspersed LiCoO 2 , facilitating to form a durable CEI with strong stability and low interface resistance. 11 ensured a stable CEI with fewer side reactions, and reduced phase collapse upon cycling at 4.6 V (vs Li/Li + ) or above. 12 Fan et al proposed a RbAlF 4 modified LCO, which demonstrated a high capacity of >220 mAh g −1 and impressive retention of >80/77% after 500/300 cycles at 30/45 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, similar surface modulation strategies have also been reported by other groups. For example, Huang’s group reported a Zr-doped and Li + conductive Li 2 Zr­(PO 4 ) 2 interspersed LiCoO 2 , facilitating to form a durable CEI with strong stability and low interface resistance . Yang’s group revealed a lattice-matched LiCoPO 4 coating on LCO, which ensured a stable CEI with fewer side reactions, and reduced phase collapse upon cycling at 4.6 V (vs Li/Li + ) or above .…”
Section: Introductionmentioning
confidence: 99%